PENERAPAN SANKSI PIDANA TERHADAP PELAKU JUDI ONLINE BOLA BERDASARKAN UU NO. 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK (STUDI PUTUSAN NOMOR 1101/PID.SUS/2021/PN JKT.UTR) - Fahrizal Fauzi; Wenny Megawati (HUKMY : Jurnal Hukum, 2025)
Gambling has developed with the changing times. Gambling which initially could only be played conventionally, now can be played online with the help of electronic media as long it can be connected to the internet. Online gambling is very popular in the community because online gambling service providers offer online gambling players if the play online gambling on services managed by the online gambling service provider, then online gambling player will be promised multiple profits. The problems contained in the research only focus on two problems, that is the application of criminal sanctions for online soccer gambling based on the decision of the North Jakarta District Court Number 1101/Pid.Sus/2021/PN Jkt.Utr and the effectiveness of ITE Law No. 19 the year 2016. The research method used is normative juridical, the data used as research material is obtained from the Supreme Court website. The results of the research show that the judge in imposing imprisonment is still relatively light. The effectiveness of ITE Law No. 19 the year 2016 can be said to still have shortcomings to prevent people from providing online gambling service.